APLIKASI RETENSI REKAM MEDIS MENGGUNAKAN MICROSOFT ACCESS - Alfauzain, Alfauzain; Srimayarti, Berly Nisa; Novita, Dian; Ridwan, Muhammad (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Medical record retention is a system that regulates the storage period for medical record files. Medical records officers are also involved in destroying medical records including in the retention process. The slow retention process resulted in a large number of medical record files piling up in storage racks so that the medical record space became narrow. Developing medical record retention applications using Microsoft Access. This research method is carried out by conducting a Literature Review with the Literature Study method. The data sources in this study were 3 journals by looking at the inclusion and exclusion categories. Analyze data in terms of similarities, inequalities, views, compare and summaries. The results of 3 literature study journals are medical record retention applications made with web-based methods and web-based imaging. The system design uses Flowmap, DFD (Data Flow Diagram) and ERD (Entity Relationship Diagram) and is implemented with the Microsoft Visual Basic.Net programming language and Microsoft Access as a DBMS (Database Management System). The medical record retention application is very helpful for officers in separating active and inactive medical record files, which are equipped with menus according to user needs. It is hoped that the next researchers on several related articles, further research is needed on designing applications using table data with server side processing.